NEW PROBIOTIC AGENT FOR THE BOWEL MICROFLORA CORRECTION IN INFANTS - E. S. Keshishyan (Вопросы современной педиатрии, 2013)
Characteristics of a new probiotic — a biological additive, developed specially for children – and indications for its usage are shown in this article.